Proceedings of the 2nd International Conference on Research of Educational Administration and Management (ICREAM 2018) 2019
DOI: 10.2991/icream-18.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

Strategy in Developing Teachers' Performance at Senior High School

Abstract: This research is focused on strategy in developing teacher's performance at Senior High School in Palopo. This research is a field research by using analytic descriptive method. Data collection is done through the process of identification of factors that contribute to the development of teacher's performance done by 3 stages. Stages of data analysis are: 1) Internal Factor Evaluation, External Factor Evaluation, and Internal External analysis; 2) SWOT matrix and; 3) Quantitative Strategy Planning Matrix (QSPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The research by Cantillon et al in found that entrepreneurial leadership provides the space to optimize the potentials and motivate subordinates to work creatively and innovatively. The principal, serving as the school manager and leader, takes the role to encourage, inspire, and support the teachers to work creatively (Mahmud & Palopo, 2019). Principal with an entrepreneurship spirit can encourage the teachers to create innovation (Sahnan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The research by Cantillon et al in found that entrepreneurial leadership provides the space to optimize the potentials and motivate subordinates to work creatively and innovatively. The principal, serving as the school manager and leader, takes the role to encourage, inspire, and support the teachers to work creatively (Mahmud & Palopo, 2019). Principal with an entrepreneurship spirit can encourage the teachers to create innovation (Sahnan, 2016).…”
Section: Introductionmentioning
confidence: 99%